A MICRO- CONTROLLER BASED MODEL FOR A REAL-TIME VEHICLE OVERLOADING PREVENTION - NJUGUNA, JAMES NDUNGU (Kabarak University, 2025)
Overloading a vehicle can have fatal effects. It occurs when a vehicle's maximum allowable weight limit is exceeded. Overloading is an unlawful offense. According to Section 56 of Kenya's Traffic Act, Cap 403, the tare weight should be used to determine whether a vehicle is actually overloading. However, on Kenyan highways, law enforcement officials tend to focus on the cargo area of the vehicle. For instance, in the case of Public Service Vehicles (PSVs), the number of passengers is utilized to determine if a vehicle is overloaded. If the vehicle has not exceeded the carrying capacity, it is incorrectly assumed to be in compliance. This misconception has led to many vehicles being on the road when overloaded, which has been linked to increased road carnage leading to death, economic loss to the country, and making those people who have been living independent lives become dependents as a result of injuries sustained during the road accidents. All other causes of road accidents, such as speeding, vehicle and road conditions, and human errors, were considered normal in this study. The proposed research study aimed to employ a preventive approach to vehicle overloading using smart microcontroller technology that would prevent the engine from starting when the vehicle's tare weight was exceeded or when the vehicle's seating capacity was exceeded. To achieve this, load cells were used for weight detection, while a Passive infrared sensor (PIR)- based motion detector was used to count the number of passengers entering or exiting the vehicle. Weaknesses in the current methods used to detect and prevent overloading were identified through a desktop research methodology aimed at providing a solution. The researcher endeavored to demonstrate how overloading would be prevented by using a microcontroller-based model. The design of the model, which emanated from the suggested solution, was developed and implemented using Design Science Research to show the feasibility of the model. The prototype was evaluated to see whether the research objectives were achieved using Proof of Concept methodology. Pilot testing showed that the functional requirements were met. An observation method was employed in data collection. The data collected was analyzed using descriptive data analysis methods. Thus, it was concluded that the general concept was workable and realistic, with the recommendation that the Kenyan government should upscale this research report and re-examine current policies to facilitate the faster deployment of the system.
Keywords: Vehicle, Integrated, Tare weight, Overloading, Microcontroller.